Acute Disseminated Encephalomyelitis - J Gordon Millichap (Pediatric Neurology Briefs, 2005)
The literature on acute disseminated encephalomyelitis (ADEM) is reviewed in an update by researchers at the University of San Francisco, CA; University of Texas Southwestern Medical Center, Dallas; and Universities in Germany.